Synthesis of Branched α‐Olefins via Trimerization and Tetramerization of Ethylene - Fabian Lukas; Paula A. Simon; Thomas Dietel; Winfried P. Kretschmer; Rhett Kempe (Advanced Science)
Abstract α‐Olefins are very important bulk and fine chemicals and their synthesis from ethylene, an abundantly available and inexpensive feedstock, is highly attractive. Unfortunately, the direct or on‐purpose synthesis of olefins from ethylene is limited to three examples, 1‐butene, 1‐hexene, and 1‐octene, all having a linear structure. Herein, the direct synthesis of 3‐methylenepentane and 4‐ethylhex‐1‐ene, branched trimerization, and tetramerization products of ethylene, respectively, is reported. Different molecular titanium catalysts, all highly active, with a selectivity toward the formation of the branched ethylene trimer or tetramer, the employment of different activators, and different reaction conditions are the key to selective product formation. The long‐time stability of selected catalysts employed permits upscaling as demonstrated for the synthesis of 4‐ethylhex‐1‐ene (52 g isolated, TON(ethylene) 10.7 · 106).